2001
DOI: 10.1161/hc3501.095215
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Matrix Metalloproteinases and Reduction in Collagen Damage in the Failing Human Heart After Support With Left Ventricular Assist Devices

Abstract: Background-Left ventricular assist device (LVAD) support of the failing heart induces salutary changes in myocardial structure and function. Matrix metalloproteinases (MMPs) are increased in the failing heart and are induced by stretch in cardiac cells in vitro. We hypothesized that mechanical unloading may affect LV plasticity by regulating MMPs and their substrates. Methods and Results-LV samples were collected from patients with dilated cardiomyopathy (DCM, nϭ14) or ischemic cardiomyopathy (ICM, nϭ16) at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
166
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(178 citation statements)
references
References 42 publications
10
166
1
1
Order By: Relevance
“…So, both WB and gel zymography showed an increase in active MMP. This change in active MMP is confirmed by others in heart failure 39,40 and during LVAD support 36 by gel zymography. WB and gel zymography differed in the detected amount of inactive MMP.…”
Section: Basement Membrane Degradation After Lvad Ah Bruggink Et Alsupporting
confidence: 82%
See 2 more Smart Citations
“…So, both WB and gel zymography showed an increase in active MMP. This change in active MMP is confirmed by others in heart failure 39,40 and during LVAD support 36 by gel zymography. WB and gel zymography differed in the detected amount of inactive MMP.…”
Section: Basement Membrane Degradation After Lvad Ah Bruggink Et Alsupporting
confidence: 82%
“…The differences in this association between the BM and collagen fibers may be due to alterations of the BM but may also be caused by the changes in the ECM. 15,36,37 With IHC, we showed a significant reduction of type IV collagen immunoreactivity in the BM after LVAD support. However, laminin was still present in the BM after unloading of the heart.…”
Section: Basement Membrane Degradation After Lvad Ah Bruggink Et Almentioning
confidence: 76%
See 1 more Smart Citation
“…15,25,[27][28][29] In the present study, chronic ISO administration resulted in marked increases in myocardial collagen concentrations and consequent increments in both soluble (noncrosslinked) and insoluble (crosslinked) myocardial collagen concentrations. This is in contrast to the myocardial collagen change noted in age-matched untreated SHR, in which although myocardial collagen concentrations were increased, the enhanced crosslinked properties of collagen (decreased solubility) resulted in increments in the crosslinked, but not in the noncrosslinked portion of myocardial collagen.…”
Section: Discussionsupporting
confidence: 54%
“…4,6 Human and animal studies have suggested that regulating the composition of ECM can provide new insights into the prevention of cardiac remodelling in ischaemia. [14][15][16] Invasive myocardial biopsy has been the gold standard for evaluating myocardial fibrosis and tissue repair. However, noninvasive ways of assessing collagen metabolism (by measuring the biomarkers MMP and TIMP) have been developed and may replace myocardial biopsy.…”
Section: Discussionmentioning
confidence: 99%